EVALUASI PENERAPAN SISTEM INFORMASI AKUNTANSI PENERIMAAN DAN PENGELUARAN KAS PADA PT. DAYA ANUGRAH MANDIRI - Pusung, Brando Nofdi; Saerang, David P.E; Wangkar, Anneke (GOING CONCERN : JURNAL RISET AKUNTANSI, 2020)
Every organization needs an information system to facilitate the activities that have been carried out planned and supervised to control the company's financial cash flow. The purpose of this study is to evaluate the accounting information system for cash receipts and disbursements and observe whether there is synchronization between the system and the existing application. The method used is a descriptive qualitative research method that research begins by collecting and observing all parts in information comes in its entirety and the details are then collaborated to get a result. The results showed that the accounting information system for cash receipts and disbursements at PT. Daya Anugrah Mandiri is quite good, although there are a few mistakes when inputting cash and consumers names, but they can fulfill important elements of the accounting information system that are human resources, equipment, forms or documents, records/notes, procedures, and reports. Cash receipts and disbursements procedures are set up and done best to avoid mistakes that might occur, so until now the accounting information system for cash receipts and disbursements of PT. Daya Anugrah Mandiri can be done effectively.